Spray-Assisted Method of Synthesis of Anode Materials for Lithium-Ion Battery - Terechshenko, Alina (Nazarbayev University School of Engineering and Digital Sciences, 2019)
The current energy and environment challenges demand an emerging renewable energy sources and green electrical transportation implementation. Both of these require rechargeable batteries to store energy and provide power. However, lithium-ion batteries (LIBs) with graphite-based anode, which is the most used anode material for current LIB technologies, cannot meet the requirements for new generation electric vehicles of different type (hybrid, plug-in or pure) and other applications such as modern communication systems, because they require two to five times more energy density than what LIBs with graphite-based anode can offer. Thus, there is an extreme need for introduction of novel materials for next generation anode for LIBs. The spinel-structured lithium titanium oxide Li4Ti5O12 (LTO) is one of the most effective active matrices for silicon (Si) to form anode and enhance the advantageous properties of both materials. One of the possibilities to efficiently combine Si and LTO, keeping their advantages and overcoming drawbacks, is to apply nanomixing. Moreover, in order to enhance conductivity of the composite, sucrose and polyethylene glycol (PEG) were added into the material as a carbon source, and their effect on its electrochemical performance was compared. One of the most suitable and promising method of LTO synthesis is the spray pyrolysis technique as there are promising opportunities to establish a continuous preparation process.